1993
DOI: 10.1093/rfs/6.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Insider Trading as a Signal of Private Information

Abstract: There is substantial evidence that insider trading is present around corporate announcements and that this insider trading is motivated by private information. Using real estate investment trusts that choose to reappraise themselves as our sample, we establish that the appraisals contain information, but find no market response to the public announcement of this information in these appraisals. We consider two possible explanations for this inconsistency: the first that the appraisal information is not highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(87 citation statements)
references
References 26 publications
4
83
0
Order By: Relevance
“…Mei and Lee (1994) further find that the real estate premium found in Liu and Mei (1992) captures the systematic risk in the real estate market rather than real estate market imperfections. Damodaran and Liu (1993) find that NAVs contain information, by showing that insiders buy (sell) after they receive favorable (unfavorable) NAV news, especially for negative appraisals. Finally, Gentry et al (2004) reveal that investors can profit from the deviations of REIT stock prices from their NAVs; using REIT data since 1990, they find large positive excess returns result from buying stocks trading at a discount to NAV, and shorting stocks 13 The square footage is reported for most properties except those that are raw land and those that are in the process of being developed (construction in progress).…”
Section: Data Descriptionmentioning
confidence: 94%
See 2 more Smart Citations
“…Mei and Lee (1994) further find that the real estate premium found in Liu and Mei (1992) captures the systematic risk in the real estate market rather than real estate market imperfections. Damodaran and Liu (1993) find that NAVs contain information, by showing that insiders buy (sell) after they receive favorable (unfavorable) NAV news, especially for negative appraisals. Finally, Gentry et al (2004) reveal that investors can profit from the deviations of REIT stock prices from their NAVs; using REIT data since 1990, they find large positive excess returns result from buying stocks trading at a discount to NAV, and shorting stocks 13 The square footage is reported for most properties except those that are raw land and those that are in the process of being developed (construction in progress).…”
Section: Data Descriptionmentioning
confidence: 94%
“…We call this argument the recessionary shock effect. 9 Finally, our data set, by allowing us to compare the real and financial market performance of office Real Estate Investment Trusts (REITs) with some New York exposure to those without any New York presence, also enables us to separate the local effects from the shocks that affected the entire U.S. office real estate market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Furthermore, REITs are well-suited for the study of agency issues related to capital structure because their tax-advantaged status, high required dividend payout, and uniform asset regulation eliminate or reduce the need to control for potentially confounding effects such as tax considerations or variations in dividend payout rates. 6 Previous studies that have used REITs to study corporate finance issues include Gentry et al (2003), Ling and Ryngaert (1997), Damodaran and Liu (1993), Wang et al (1992), Jaffe (1991), Shilling and Howe (1988), and Allen and Sirmans (1987).…”
Section: Introductionmentioning
confidence: 99%
“…First, this paper uses insider trading prior to the announcement of equity-selling mechanisms to measure the other insiders' decision. This is because most studies indicate signi cant changes in insider trading patterns before equity-offering announcement (Karpoff and Lee (1991), Kahle (2000), Clarke, Dunbar, and Kahle (2001), Lee (1997)) and researchers have concluded that insider trades reveal important non-public information (John and Mishra (1990), Damodaran and Liu (1993), Seyhun (1986), Meulbroek (1992)). Second, this paper uses both the two-stage estimation approach and the conditional correlation approach.…”
Section: Introductionmentioning
confidence: 99%